2016
DOI: 10.1016/j.cgh.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Features and Progression of Potential Celiac Disease in Adults

Abstract: In a 3-year study of adults with potential celiac disease, we found most to have symptoms, but these improved on gluten withdrawal. Conversely, we do not recommend a gluten-free diet for asymptomatic adults with potential celiac disease because they do not tend to develop villous atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
69
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 22 publications
7
69
1
3
Order By: Relevance
“…Microscopic evaluation showed Marsh 0 histology in 37.5% of patients and Marsh 1 histology in 62.5%. These findings were in line with previous studies [12,[14][15][16][17]: the high rate of first-degree relatives with CD and the high predominance of symptomatic patients could actually explain an increase in serological investigations for CD suspicion and, as consequence, an increase in the prevalence of PCD over time. More specifically, Volta et al [17], Biagi et al [14] and Zanini et al [13] have reported a PCD prevalence of 10.5%, 18.3% and 11%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Microscopic evaluation showed Marsh 0 histology in 37.5% of patients and Marsh 1 histology in 62.5%. These findings were in line with previous studies [12,[14][15][16][17]: the high rate of first-degree relatives with CD and the high predominance of symptomatic patients could actually explain an increase in serological investigations for CD suspicion and, as consequence, an increase in the prevalence of PCD over time. More specifically, Volta et al [17], Biagi et al [14] and Zanini et al [13] have reported a PCD prevalence of 10.5%, 18.3% and 11%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Volta and colleagues [17] reported in their series of CD patients a population of adults with normal mucosa, finding no significant difference between this population and that with Marsh 1 in terms of clinical features. In line with these Authors' findings, we did not detect any differences between the two groups at the time of PCD diagnosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, nowadays forthcoming celiac patients are often found even before the development of villous atrophy [41,44]. This is relevant in the context of liver function, as we now discovered increased ALT to be more common in children with advanced enteropathy.…”
Section: Discussionmentioning
confidence: 86%
“…Another factor promotive of reduced diagnostic delay is decentralization of the first-line case-finding from tertiary to primary care [40]. Most previous studies [33,35,[41][42][43] have been conducted in special centres and severe presentation has probably been overrepresented. Accordingly, in our earlier adult study, which also showed a low prevalence of increased liver values, most patients had mild presentation [17].…”
Section: Discussionmentioning
confidence: 99%